KONSEP TUHAN DALAM EPISTEMOLOGI ISLAM (Studi Atas Pandangan Hidup Sebagai Asas Epistemologi) - Asmu'i, Asmu'i (Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
Islamic epistemology develops upon the Islamic worldview, which centers on the concept of God. This divine concept integrates all activities, scientific theories and aspects of life, reflecting the unity of God (Tawhid). All disciplines and life aspects culminate in acknowledging God's omnipotence. God's concept serves as the benchmark for truth and happiness. The universe is considered God's signs, guiding humanity toward knowing and worshiping Allah. These realities shape Islamic epistemology, encompassing reality, truth, knowledge definition, methodology and comprehension. This article fundamentally highlights the distinction between Islamic and Western epistemologies. Western epistemology undergoes significant changes alongside societal shifts, challenging God's authority, especially in scientific pursuits. This culminates in the postmodern conclusion: